A single amino acid change in the glycoprotein of lymphocytic choriomeningitis virus is associated with the ability to cause growth hormone deficiency syndrome. - Teng, M N (1996)
Persistent infection of C3H/St mice with certain strains of lymphocytic choriomeningitis virus (LCMV) causes a growth hormone (GH) deficiency syndrome (GHDS) manifested as growth retardation and hypoglycemia. Infected mice show high levels of viral replication in the GH-producing cells in the anterior pituitary leading to decreased synthesis of GH mRNA and protein despite the absence of detectable virus-induced cell structural damage. Virus clones isolated from the GHDS-negative LCMV WE strain can cause the disease, while others cannot. The genetic basis of this phenotypic difference is a nucleotide substitution resulting in a single amino acid difference in the viral glycoprotein. Reassortant studies indicate that the single amino acid substitution (Ser-153 to Phe) is sufficient to allow infection of the GH-producing cells and cause GHDS. These results show that a single change in the genome can affect viral pathogenicity by altering the tropism of the virus.